Evaluación del efecto del agua magnetizada en la primera fase del desarrollo fenológico de quinua (Chenopodium quinua) variedad pata de venado, Latacunga-Cotopaxi, 2021 - Lino Quishpe, Jorge Manuel (2021)
This research was performed at the Salache Academic Experimental Centre of the Technical University of Cotopaxi, as part of the Intelligent Greenhouse and Andean Grains research projects, at an altitude of 2733 m.a.s.l., with the following objectives: to characterise the agronomic behaviour of quinoa plants with the application of magnetised water. To analyse the behaviour of the physical-chemical properties of the soil and water when subjected to magnetic fields. A Randomised Complete Block Design was applied with 4 treatments and 16 experimental units. Magnetised water was supplied at 3 intensities, (T2: 1000 gauss neodymium magnet; T3: 2 magnets (one neodymium and one mineral magnet 3000 gauss), T4 magnets (1 neodymium magnet plus two mineral magnets 5000 gauss) and a control (no magnetic field). For the water supply, a tensiometer was used to determine the field capacity and to irrigate for approximately 20 minutes per treatment. The water analysed after being treated with magnetisation manifests that there is variation showing that there are changes in the chemical properties compared to the untreated water. Water parameters change when subjected to magnetic fields, as a result, pH and hardness decrease with increasing magnet intensity with initial pH 8.02 and a hardness of 254 at T1. The most effective treatment is T4, the pH level drops to 7.9, its hardness level to 146, which is moderately hard. In the degree of restriction concerning to electrical conductivity from 419 to 420. The soil parameters do change when water is supplied to the soil subjected to magnetic fields, the results of PH and Electrical Conductivity. In the T3 treatment, the pH is 8.26 and increases its level of 0.32 in electrical conductivity.